Forms of health system fragmentation during conflict: the case of Yemen - Dureab, Fekri; Hussain, Taha; Sheikh, Rashad; Al-Dheeb, Najwa; Al-Awlaqi, Sameh; Jahn, Albrecht (Frontiers in Public Health, 2021)
The continuous and protracted conflict in Yemen has evolved into the worst humanitarian situation in the modern history. All public structures in the country, including the health system and its basic functions, have been under tremendous pressures. One of the key obstacles is fragmentation of health system. This study aims at exploring The continuous and protracted conflict in Yemen has evolved into the worst humanitarian situation in the modern history. All public structures in the country, including the health system and its basic functions, have been under tremendous pressures. One of the key obstacles is fragmentation of health system. This study aims at exploring and documenting the forms of health system fragmentation in humanitarian and conflict affected contexts by studying Yemen as a case study. We collected national qualitative data from key informants through in-depth interviews. A pool of respondents was identified from the Ministry of Health, donors, and non-governmental organizations. Data was collected between May and June 2019. We interviewed 8 key informants and reviewed national health policy documents and references provided by key informants. Interviews were recorded, transcribed, and analyzed using qualitative content analysis. We further conducted a literature review to augment and triangulate the findings. Six themes emerged from our data sets and analysis, representing various forms of fragmentation: political, structural, inter-sectoral, financial, governance and health agenda-related forms. Health system fragmentation in Yemen existed before the conflict eruption and has aggravated as the conflict evolves. The humanitarian situation and the collapsing health system enabled the influx of various national and international health actors. In conclusion; the protracted conflict and fragile situation in Yemen have accentuated the fragmentation of health system. However, lessons showed several opportunities for more integration and contribution of achieving universal health coverage.
Gesehen am 05.08.2021